Conservation of priority woody species on farmlands: A case study from Nawaikoke sub-county, Uganda - Tabuti, John R.S.; Muwanika, Vincent B.; Arinaitwe, Mary Z.; Ticktin, Tamara (Applied Geography, 2011)
In tropical Africa, woody species provide products and services that millions of people depend on. However, many of these species are also threatened and declining and this can have serious livelihood consequences for communities who depend on them. Identifying which species are most at risk and which ones are being conserved is therefore critical. In this study, we undertook a survey in Nawaikoke Sub-county, Uganda to assess which of 26 most preferred species are managed on farmland, to identify what environmental factors influence their availability, and to describe their conservation statuses. Individuals of these species were enumerated and measured in 320 plots across the eight parishes of Nawaikoke. Seven of the 26 species were not encountered in any plots. The rest were found close to homesteads in homegardens, in crop gardens and in young fallows on well drained soils. Only Combretum collinum and Acacia seyal were associated with old fallows and poorly drained clay loamy soils. Mangifera indica, Milicia excelsa, Ficus natalensis, Ficus sycomorus, Artocarpus heterophyllus and Albizia coriaria were found in numerous plots in at least six of the eight parishes, and at relatively high densities and we consider them to be at the lowest risk of disappearance from the landscape. Size-class distributions of all preferred species, regardless of their abundance, exhibited little recruitment from juvenile life stages. We conclude that most of the species face some level of threat through destruction of seedlings and saplings and that for these species to persist into the future there is need to work with farmers to encourage them to plant or spare those found growing naturally. There is a high potential for these species to increase in abundance because they grow in a wide diversity of farm niches. For the farmers to become more involved, focus should primarily be on native species that provide shade, fruits and timber. Some of these target species also play ecological roles, increasing their functionality. Lastly, there is need to protect non-crop habitats like fallows and wetlands.
Keywords: Agroforestry; Tree management Fallows; Tree products